Contributions Learning Strategy Problem Based Learning and Discovery Learning Independence Against Children Seen From Availability Equipment Biology Education Class X SMAN 2 in Salatiga in the Academic Year 2015/2016 - SULISTYANINGSIH, Sulistyaningsih; , Prof. Dr. Sutama, M.Pd; , Dr. Sofyan Anif, M.Si (2016)
The objectives of this study was to test: 1) the difference of students' independent between Problem Based Learning and Discovery Learning. 2) the difference of learning activity between the well-equiped and not-well-equiped in learning Biology. 3) The interaction between the using of learning strategy with the study independent and the learning equipment availability. This study was experimental study. The variable of this study were dependent variable which was learning activity, the independent variable which were the PBL and the DL, and the moderator variable was the learning equipment availability. The population of this study was all of the students of grade X in SMA N 2 Salatiga in number of 308 students. The sample of this study were grade X1 of 35 students and grade X3 of 35 students which were choosen by using cluster random sampling. The data collection was using questionair and the data analysis was using T-Test. Based on the study, the result showed that: 1) the PBL gave a better influence than the DL toward the students' independent in learning activity, this was shown by the result of T-test = 65,988 > Ttable = 2,000 where the average result of the PBL, 88,400 higher than the average result of the DL which was 81,0286. 2) the students with well-equiped tool gave better influence than those with not-well-equped tools toward the students' learning independent with the result Ttes = 68,202 > Ttable = 2,000 where the average result of the PBL equipment availability 88,7143 higher than the DL equipment availability which was 79,48 57. 3) The learning strategy and the availability of the equipment has the influence interaction that very significant toward the learning independent. This was shown by the result of learning independent with the Ttes = 9,225 > Ttable = 3,98 because Ftest > Ftable of 9.225 > 3,98, meanwhile based on the availability of the learning equipment got the result of Ftest =17, 313.